2020
DOI: 10.1590/s2175-97902019000318388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of daidzein on Parkinson disease induced by reserpine in rats

Abstract: Parkinson disease is a neurodegenerative disorder characterised by the cardinal symptoms of stiffness, resting tremor, slowness (bradykinesia) and reduction of movement (hypokinesia). Involvement of oxidative damage has been reported in the pathophysiology of Parkinson disease and its related complications. The purpose of this study was to examine the effect of daidzein to quench the free radicals produced as a result of the increased oxidative stress in Parkinson disease.Parkinson disease is induced by admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
2
11
0
1
Order By: Relevance
“…In this study, we employed a reserpine-induced animal model of PD that reflect aspects of PD neuropathology and mimics the human PD 23 , 37 . Reserpine, a potent VMAT2 inhibitor, induces muscular rigidity, tremors, and akinesia by depletion of central catecholamine storage 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we employed a reserpine-induced animal model of PD that reflect aspects of PD neuropathology and mimics the human PD 23 , 37 . Reserpine, a potent VMAT2 inhibitor, induces muscular rigidity, tremors, and akinesia by depletion of central catecholamine storage 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Daidzein treatment at a dose of 50 and 100 mg/kg significantly reduced reserpine‐induced tremor, rigidity, akinesia, and oxidative damage. Histopathological findings also confirmed that daidzein prevents neuronal degeneration in brain tissue (Goel & Chaudhary, 2020). The effect of daidzein on scopolamine‐induced cognitive impairment in male mice has also been studied, it was observed that daidzein treatment at dose 5 mg/kg significantly improved cognitive impairments via estrogen receptor which prevented neuron from oxidative damage (Kim et al, 2010).…”
Section: Pharmacological Activities Of Daidzein (Figure 7)mentioning
confidence: 65%
“…It has been illustrated that daidzein (DZ) in combination with levodopa (L‐dopa) and carbidopa produced a significant reduction in the symptoms of reserpine‐induced PD that included muscular rigidity, tremors, and akinesia. Also, DZ significantly reduced the levels of lipid peroxidation and caused an increase in the GSH level suggesting that DZ can exert a neuroprotective efficacy in PD via restoring the level of DA and protection of dopaminergic neurons against apoptosis due to regulation of the antioxidant system (Goel & Chaudhary, 2020) (Figure 4).…”
Section: Molecular Targets Of Phytoestrogen‐isoflavones In Neurodegen...mentioning
confidence: 99%